Classroom Discourse Analysis on Language Interaction at The First Level Class of STAR English Course Parepare - Kasmiati Usman; Mujahidah (Institut Agama Islam Negeri Parepare, 2021)
Language is taking a place as the main connector among the teacher and students in the teaching-learning process. The study of language that is related to teacher’s language interaction in classroom teaching is called classroom discourse analysis. Study on classroom discourse structure firstly introduced by Sinclair and Coulthard by developing a model of discourse involving five levels in hierarchical order - from the lowest to the highest acts, move, exchange, transaction and interaction unit where the higher unit contains the lower ones.This research aimed to know what kind of the act structure that the students and teacher used in the Classroom based on Sinclair and Coulthard Rank Scale, also needed to be known which one of them dominantly used in interaction. The result of the research found that there were several types of Act Structure used in the Classroom interaction such as Marker, Starter, Elicitation, Check, Directive, Informative, Prompt, Clue, Cue, Bid, Nomination, Acknowledge, Reply, React, Accept, Evaluate, Silent Stress, Meta statement, and Conclusion. The total numbers of Act Structure in the observation which have been done are 652 acts. Then, the type of Act Structure dominantly used is Elicitation (/el/) which around 14,7 % dominated the classroom interaction.